The Interconnection of Islamic Ethics and Economic Practice: A Bibliometric Analysis - Zuwardi, Zuwardi; Judijanto, Loso; Al-Amin, Al-Amin; MS, Syaifullah; Irnayenti, Irnayenti; Doni , Saputra (Universitas Pendidikan Ganesha, 2025)
This study presents a comprehensive bibliometric analysis of research investigating the linkages between Islamic ethics and economic practices from 2015 to 2024, utilizing data from the Scopus database. The analysis examined 241 documents to identify publication patterns, influential authors, geographic distribution, and thematic evolution in the field. The results revealed a steady increase in the study results, with peak publications occurring in 2022-2023 (30 documents annually). Malaysia and Indonesia emerged as leading research contributors, collectively accounting for 35% of publications. Journal articles dominated the type of publication (73.9%), followed by book contributions (16.6%). Network analysis identifies different research groups centered around Islamic banking, sustainable finance, and ethical business practices. The study found that while traditional Islamic principles remain fundamental, research has evolved to address contemporary challenges such as digital transformation, sustainability, and post-pandemic economic recovery. Analysis of citations reveals that the practical application of Islamic ethics in the modern financial system has received significant attention, with authors such as Alserhan, B.A. (50 quotes) and Ali, A.J. (42 quotes) emerging as influential contributors. These findings demonstrate a growing academic interest in integrating Islamic ethical principles with contemporary economic practices while highlighting research gaps in areas such as financial technology and standard ethical frameworks. This analysis contributes to understanding the current state of Islamic economic ethics research and suggests directions for future investigations